Information technology adoption inhibitor-influencer model for SMEs in the construction industry - Ibrahim, Magaji Umar (2018)
Small and Medium Enterprises (SME) in the Nigerian construction industry has been struggling with the issues of improper materials management practices. In an attempt to address these issues, Information Technology (IT) was initiated primarily to overcome the shortcomings of the conventional materials management practices. Although, IT was aimed to greatly enhance performance and reduce non-value adding activities, IT structures in reality lack clear adoption realisation process to drive in within such factors to deliver the adoption of IT in SMEs. The current trend of materials management practices in small and medium construction companies has been the subject of criticism. IT adoption has not had the expected resounding success of a total adoption and utilisation. This research has empirically identified factors inhibiting and influencing IT adoption in Nigerian SMEs. The research focuses on the factors with respect to their inhibiting and influencing impact to IT adoption within the context of SMEs in Nigeria with the aim to develop IT adoption inhibitor-influencer model for SME’s IT adoption enhancement. The methodology adopted in this research was mixed methods approach. Interview data was obtained from seven (7) SMEs, based on a systematic sampling of the SMEs in the north-eastern region of Nigeria and the data were analysed using content analysis. Whilst questionnaire survey data was obtained from 187 respondents and the data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) to test the relationships between the exogenous constructs (inhibitor and influencer) to endogenous construct in order to validate and confirm the developed influencing factors for IT adoption model. The findings reveal that cost, government, and employees factors have significant influence on SME’s IT adoption, whilst, technology and practices factors were found to have a partial inhibiting effect on SME’s IT adoption. This research provides a multi-dimensional perspective for the enhancement of SME’s IT adoption and can contribute to high project performance. It is also provide mechanism for realising effective materials management practices for delivering successful projects in the SME construction companies. In conclusion, it is timely to reverse the trend of low IT adoption within SMEs in the construction industry in Nigeria.